Comparative metabolic footprinting of a large number of commercial wine yeast strains in Chardonnay fermentations. Issue 4 (12th April 2013) - Richter, Chandra L.; Dunn, Barbara; Sherlock, Gavin; Pugh, Tom
Abstract Wine has been made for thousands of years. In modern times, as the importance of yeast as an ingredient in winemaking became better appreciated, companies worldwide have collected and marketed specific yeast strains for enhancing positive and minimizing negative attributes in wine. It is generally believed that each yeast strain contributes uniquely to fermentation performance and wine style because of its genetic background; however, the impact of metabolic diversity among wine yeasts on aroma compound production has not been extensively studied. We characterized the metabolic footprints of 69 different commercial wine yeast strains in triplicate fermentations of identical Chardonnay juice, by measuring 29 primary and secondary metabolites; we additionally measured seven attributes of fermentation performance of these strains. We identified up to 1000‐fold differences between strains for some of the metabolites and observed large differences in fermentation performance, suggesting significant metabolic diversity. These differences represent potential selective markers for the strains that may be important to the wine industry. Analysis of these metabolic traits further builds on the known genomic diversity of these strains and provides new insights into their genetic and metabolic relatedness.